Case Report: A Case of a Child With Facial Foreign Body Abscess and Facial Artery Pseudoaneurysm - Kuang, Rong; Zhou, Jing; Deng, Jiaqi; Xia, Tian; Li, Mingxing (Frontiers in Pediatrics, 2022)
Facial artery pseudoaneurysms are rare and mostly a result of blunt injury. Since the facial arteries are well protected by facial soft tissue and the lumen of the facial artery is thin and small in diameter, a sharp injury usually leads to complete transection rather than partial laceration of the blood vessel. As a non-invasive method, ultrasound does not involve radiation and sedation, and has diagnostic value for pseudoaneurysms, particularly for the examination of facial artery pseudoaneurysms in children. Here, we report a case of facial foreign body abscess and facial artery pseudoaneurysm in a 19-month-old child one week after a sharpness injury that was diagnosed by ultrasound.